(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the effect of the Gardens of Ideas method on the creative thinking of female studentsFifth grade literary in the subject of history.And to achieve this goal; (50) female students were selected and distributed into two groups, one of which was an experimental one that consisted of (24).A female student studied using the Gardens of Ideas method, and the other was a control group of (26) female students who studied the methodtraditional. Behavioral objectives, instructional plans, and the research tool represented by the thinking test were preparedCreative dish at the end of the experiment.After correcting and processing the data statistically, the results showed that the experimental group was superiorBy using the Gardens of Ideas method on the control group that was taught in the traditional wayThe level of thinking of literary fifth grade students in the subject of history.In the light of the research results, the researcher presented a set of recommendations and proposals.